Bioequivalence of a biosimilar enoxaparin (Cloti‐Xa™) and its innovator (Clexane®): A single‐dose, randomized, double‐blind, two‐period, two‐treatment, two‐sequence, crossover, balanced study in healthy human subjects - Sumit Saxena; Manu Chaudhary; Saransh Chaudhary; Anmol Aggarwal (Wiley, 2022)
Abstract Currently, several biosimilars of low‐molecular‐weight heparins (LMWHs) with differing potencies are being developed and marketed globally. Thus, it is important that the potency of each biosimilar LMWH be compared with its innovator's molecule. The present study aimed to determine the bioequivalence of biosimilar (Cloti‐Xa™) and innovator (Clexane®) formulations of enoxaparin sodium (40 mg/0.4 ml) in healthy human volunteers. It was conducted as a single‐dose, randomized, double‐blind, two‐period, two‐treatment, two‐sequence, crossover, balanced, pharmacodynamic study (NCT05265676). The participants were sequentially and randomly administered subcutaneous injections of Cloti‐Xa™ (test) and Clexane® (reference), separated by a one‐week washout period. To assess the Anti‐Xa & Anti‐IIa activities, tissue factor pathway inhibitor (TFPI) release and activated partial thromboplastin time (aPTT), blood samples were obtained at various timepoints upto 24 h after the drug administration. Bioequivalence was concluded if the two‐sided 90% CI for the test to reference ratio of the population is within 80%-125% for each of the Ln‐transformed values of Amax and AUECt for Anti‐Xa and Anti‐IIa. TFPI and aPTT data were submitted as supportive evidence. The study sample consisted of twenty‐four male participants. The 90% CIs of Amax and AUECt for Anti‐Xa activity were 105.50%-113.90% and 103.97%-112.08%, and for Anti‐IIa activity were 106.56%-117.90% and 107.35%-124.86%, respectively. In addition, the 90% CI of the ratio of Anti‐Xa/Anti‐IIa activity falls within the acceptance criteria. TFPI and aPTT profiles were similar for both products. No serious adverse events were observed during the study. Conclusively, the results showed that Cloti‐Xa™ and Clexane® are bioequivalent and well‐tolerated.